Aerophilic Surfaces for Sustained Corrosion Protection of Metals Underwater - Prado, Lucia; Hayek, Samer; Mazare, Anca Valentina; Erceg, Ina; Sarau, George; Christiansen, Silke; Kamaleev, Maksim; Wurmshuber, Michael; Lohbauer, Ulrich; Goldmann, Wolfgang; Virtanen, Sannakaisa; Tesler, Alexander (Advanced Functional Materials, 2024)
Corrosion and biofouling are wetting-related phenomena that limit the effective use of metals in aqueous media. Nonwettable surfaces can mitigate the adverse effects of wetting by minimizing contact with water. However, current achievements in this field fall short of meeting industrial requirements due to the short lifetime of plastrons. This study proposes a method to measure the protective sustainability of plastron. Superhydrophobic (SHS) and aerophilic (APhS) surfaces are constructed on lightweight aluminum and are initially analyzed by conventional goniometry, which show comparable values. However, the plastron that develops underwater is substantially different. While SHS exhibit unevenly broken plastron, APhS show uniform, continuous plastron. As an example of the sustained protective performance of plastron, the corrosion resistance of SHS and APhS is presented. Potentiodynamic polarization, impedance spectroscopy, and long-term immersion in seawater show a drastic enhancement in corrosion resistance, exclusively for APhS. In fact, almost no electrochemical signals are measurable, and no pitting corrosion is observed after 415 days of immersion in seawater. Conversely, SHS show no noticeable improvement and corrode faster than bare Al due to plastron loss. Since goniometric measurements do not provide information on plastron, it is essential to analyze the plastron for any non-wettable surface utilized underwater.<br
Keywords: air plastron; aluminum; Cassie–Baxter wetting; corrosion; superhydrophobic surfaces; underwater

Lateral Spacing of TiO2 Nanotube Coatings Modulates In Vivo Early New Bone Formation - Negrescu, Andreea Mariana; Ionascu, Iuliana; Necula, Madalina Georgiana; Tudor, Niculae; Kamaleev, Maksim; Zarnescu, Otilia; Mazare, Anca Valentina; Schmuki, Patrik; Cimpean, Anisoara (Biomimetics, 2025)
Due to the bio-inert nature of titanium (Ti) and subsequent accompanying chronic inflammatory response, an implant’s stability and function can be significantly affected, which is why various surface modifications have been employed, including the deposition of titanium oxide (TiO2) nanotubes (TNTs) onto the native surface through the anodic oxidation method. While the influence of nanotube diameter on cell behaviour and osteogenesis is very well documented, information regarding the effects of nanotube lateral spacing on the in vivo new bone formation process is insufficient and hard to find. Considering this, the present study’s aim was to evaluate the mechanical properties and the osteogenic ability of two types of TNTs-based pins with different lateral spacing, e.g., 25 nm (TNTs) and 92 nm (spTNTs). The mechanical properties of the TNT-coated implants were characterised from a morphological point of view (tube diameter, spacing, and tube length) using scanning electron microscopy (SEM). In addition, the chemical composition of the implants was evaluated using X-ray photoelectron spectroscopy, while surface roughness and topography were characterised using atomic force microscopy (AFM). Finally, the implants’ hardness and elastic modulus were investigated using nanoindentation measurements. The in vivo new bone formation was histologically evaluated (haematoxylin and eosin—HE staining) at 6 and 30 days post-implantation in a rat model. Mechanical characterisation revealed that the two morphologies presented a similar chemical composition and mechanical strength, but, in terms of surface roughness, the spTNTs exhibited a higher average roughness. The microscopic examination at 1 month post-implantation revealed that spTNTs pins (57.21 ± 34.93) were capable of promoting early new bone tissue formation to a greater extent than the TNTs-coated implants (24.37 ± 6.5), with a difference in the average thickness of the newly formed bone tissue of 32.84 µm, thus highlighting the importance of this parameter when designing future dental/orthopaedic implants.
CRIS-Team Scopus Importer:2025-03-14
Keywords: in vivo new bone formation; intertube spacing; nanotopographic surfaces; osteoblasts; TiO

Low pH-Induced Activation of Single-Atom Pt Sites on TiO2 for Enhanced Photocatalytic H2 Evolution - Kamaleev, Maksim; Kim, Hyesung; Denisov, Nikita; Tesler, Alexander (ACS Applied Energy Materials, 2024)
The application of single atoms (SAs) has emerged as a cutting-edge approach to the cost-efficient utilization of noble metals in catalytic processes. However, the performance of SA systems under various acidity conditions has been barely investigated. Here, we use Pt SA cocatalysts anchored on thin TiO2 films as a model system, which shows a 2.3-3.2-fold enhanced H2 evolution performance at pH = 1, as compared to less acidic conditions (pH = 6 and 14, respectively), with a remarkable turnover frequency (TOF) of up to 589 #H2 site-1 s-1. Based on variations in H2 evolution performance at different pH and Pt loadings, it is clear that activation of additional Pt sites takes place in acidic conditions, which is ascribed to changes in H-binding energy. This allows better utilization of Pt SAs at high loadings and low light intensities. Despite the partial agglomeration of Pt SAs, within 4 h, a steady surface configuration of Pt sites with abundant SAs is established, which correlates with the stabilization of the H2 evolution rate. This research demonstrates a route to extend the limit of photocatalytic H2 generation with suitable SAs and reaction conditions.
CRIS-Team Scopus Importer:2024-10-25
Keywords: hydrogen evolution reaction; pH dependence; photocatalysis; single-atom cocatalysts; TiO